Saul und der hrm: Beobachtungen zu den hrm-Konzepten in 1Sam 15 - Giercke-Ungermann, Annett (Biblische Notizen, 2014)
This study investigates both concepts of ~rx, which are contextualised in 1Sam 15. It argues that the understanding of ~rx as shown by Saul is put in contrast to the second concept of ~rx that is connec-ted to the figures of Samuel and YHWH. During the course of the narration the Sauline concept of ~rx is not only revealed as wrong by Samuel and YHWH, but by Saul himself.